2010
DOI: 10.1017/s0033822200044994
|View full text |Cite
|
Sign up to set email alerts
|

Dating Human Occupation on Diatom-Phytolith-Rich Sediment: Case Studies of Mustang Spring and Lubbock Lake, Texas, USA

Abstract: ABSTRACT. The Great Plains of North America have a rich archaeological record that spans the period from Late Glacial to Historic times, a period that also witnessed significant changes in climate and ecology. Chronometric dating of archaeological sites in many areas of the Great Plains, however, is often problematic, largely because charcoal and wood-the preferred materials for radiocarbon dating-are scarce in this grassland environment with few trees. Two reference archaeological sites are studied here: Must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…For rice crop phytoliths, it has been found that the original physical characteristics are significantly altered when the extraction temperature exceeds 900°C 41 . Previous studies indicated that the relationship between the 14 C age and combustion temperature can be used to quantify the relative contributions of different pools of organic carbon 29 30 31 . For phytoliths in AD 2012 rice straw, the F m of PhytOC was depleted by approximately 4% when the sample was combusted below 1100°C and was even more depleted (to approximately 12%) when combusted over 1400°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For rice crop phytoliths, it has been found that the original physical characteristics are significantly altered when the extraction temperature exceeds 900°C 41 . Previous studies indicated that the relationship between the 14 C age and combustion temperature can be used to quantify the relative contributions of different pools of organic carbon 29 30 31 . For phytoliths in AD 2012 rice straw, the F m of PhytOC was depleted by approximately 4% when the sample was combusted below 1100°C and was even more depleted (to approximately 12%) when combusted over 1400°C.…”
Section: Discussionmentioning
confidence: 99%
“…The exact influence of these two components of PhytOC on 14 C dating needs to be examined in detail because previous attempts to date 14 C PhytOC have focused on the total organic matter within the phytolith, and these attempts have clearly failed. In some cases, the combustion temperature can be used to separate heterogeneous mixtures of labile and refractory carbonaceous components, each of which may have a different apparent radiocarbon age 29 30 31 . Recently, a more robust phytolith extraction protocol suitable for carbon isotopic analysis was reported 32 , and we use this protocol to further investigate the potential source of PhytOC.…”
mentioning
confidence: 99%
“…1). Lubbock Lake is a well-stratified archaeological site, discovered in 1936, that contains evidence of occupation by Native American populations beginning as early as 11,100 14 C yr BP (Holliday, 1985a;Johnson, 1987;Hatte et al, 2010). The Paleoindian-aged archaeological deposits are associated with alluvial, spring, marsh, and lacustrine sediments, and include Rancholabrean faunal remains with evidence of butchering (Johnson and Holliday, 1981;Stafford, 1981;Holliday, 1985a).…”
Section: Lubbock Lake Texasmentioning
confidence: 99%
“…In the case of silicates minerals (e.g. phytoliths and diatoms), recent studies indicate that these materials interact with the CO 2 in the environment and change the original 14 C content (Hatté et al 2010;Santos et al 2010). Furthermore, when dealing with archaeological ash samples, a serious difficulty is the problem encountered by Koumouzelis et al (2001) and when dating calcitic plaster/mortar (Lindroos et al 2007), namely that the crystals are relatively unstable and undergo diagenetic alteration that results in the original 14 C concentration changing over time.…”
Section: Introductionmentioning
confidence: 99%